2008
DOI: 10.1177/1084713807306241
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Screening and Diagnostic Evaluation of Children With Unilateral and Mild Bilateral Hearing Loss

Abstract: More than 90% of newborns in the United States are now being screened for hearing loss. A large fraction of cases of unilateral hearing loss and mild bilateral hearing loss are not currently identified through newborn hearing screening. This is of concern because a preponderance of research has demonstrated that unilateral hearing loss and mild bilateral hearing loss can lead to developmental delays and educational problems for some children. To help address this probable underidentification of unilateral hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
16

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 35 publications
(55 reference statements)
1
28
0
16
Order By: Relevance
“…This may be especially true in the case of parents of children with mild HL, who frequently observe responses to environmental sounds and speech. It is also possible that parents may interpret the use of the term mild HL as an indication that the magnitude of the HL is insignificant and that immediate follow-up is not critical (Haggard & Primus, 1999;Ross et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be especially true in the case of parents of children with mild HL, who frequently observe responses to environmental sounds and speech. It is also possible that parents may interpret the use of the term mild HL as an indication that the magnitude of the HL is insignificant and that immediate follow-up is not critical (Haggard & Primus, 1999;Ross et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the basis of the expected prevalence, not all children with mild HL are identified during the newborn period. Ross et al (2008) reported that newborn prevalence of mild HL is 0.16/1,000 live births on the basis of data reported by state Early Hearing Detection and Intervention organizations, but the actual prevalence is 0.36/1,000 live births (Watkin & Baldwin, 1999). The lower rate of identification is due in part to the fact that hearing screening protocols focus on detecting greater than mild levels of HL to reduce the number of false positives (White & Muñoz, 2008).…”
Section: Effects Of Cumulative Auditory Experiencementioning
confidence: 99%
“…Approximately 98% of eligible infants born in the United States are now being screened for HL at birth (U.S. Centers for Disease Control, 2011), which has led to dramatic reductions over the past two decades in the age at identification of HL for children who are hard of hearing (Harrison & Roush, 1996;Holte et al, 2012). Although the vast majority of infants are being screened for HL, an often stated concern is that children with mild HL are more likely to be underidentified or later identified compared with children with moderate-to-profound HL (Johnson et al, 2005;Ross et al, 2008). Late identification leads to later intervention (or no intervention at all), which puts children with mild HL at risk for academic, language, and social delays (Bess, Dodd-Murphy, & Parker, 1998;Blair et al, 1985;Most, 2004;Walker, Holte, et al, 2015;Yoshinaga-Itano et al, 2008).…”
Section: Nhs and Mild Hlmentioning
confidence: 99%
“…These outcomes differ from the 2009 sample, which included initial ABR thresholds indicating that there were three infants with bilateral moderate hearing loss, one with bilateral profound hearing loss, and one with auditory neuropathy. Although it has been noted that current hearing screening protocols are likely to miss unilateral and mild bilateral hearing losses (Ross et al, 2008), three of the six infants identified with hearing loss (Infants 1, 3, and 4) fell in this category. Infant 1 had a mild-moderate unilateral hearing loss and despite recommendation for a hearing aid fitting was counseled by the otolaryngologist that he did not need a hearing aid because he had normal hearing in one ear.…”
Section: Amplification Within 1 Month Of Diagnosismentioning
confidence: 94%